ANALYSIS THE INFLUENCE OF DIGITAL MARKETING AND SALES PROMOTION ON CUSTOMER PURCHASE INTENTION FOR SKINTIFIC PRODUCTS AT TIKTOK SHOP - Kartini Alineke Sabanari; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to analyse the effect of digital marketing and sales promotion on customer purchase intention for Skintific products at TikTok Shop, an Indonesian skincare brand currently popular on TikTok. The independent variables in this study are Digital Marketing and Sales Promotion, while the dependent variable analysed is Customer Purchase Intention. This research uses a quantitative method with a sample of 100 respondents who are Generation Z and Millennial active TikTok users. Data was collected through a questionnaire with a Likert scale. The results of this study indicate that Digital Marketing and Sales Promotion synergistically and significantly influence customer Purchase Intention. The combination of innovative digital marketing strategies with attractive sales promotions on e-commerce platforms is proven to play an important role in increasing purchase intention.   Kata Kunci: Digital Marketing, Sales Promotion, Purchase Intention